Pemetaan Sosial dalam Perencanaan Pembangunan Desa Berkelanjutan: Studi Desa Srigonco, Malang - Leksono, Didit Puji; Purborini, Vivi Sylvia; Suryanatha, Ida Bagus; Kaharap, Yorgen; Raysharie, Puput Iswandyah (Abdimas Indonesian Journal, 2025)
Social mapping is a crucial instrument in village development planning based on the real conditions of the community. This study aims to describe the results of social mapping as the basis for sustainable village development planning in Srigonco Village, Malang Regency. This research employed a qualitative approach using in-depth interviews with 42 respondents consisting of village leaders and community members. Social mapping was conducted based on nine pillars, namely socio-cultural, socio-economic, education, health, law, community empowerment, entrepreneurship (MSMEs), women-children-disabilities, as well as environment and infrastructure. The findings indicate that Srigonco Village has considerable potential in the agricultural, livestock, fisheries, tourism, and MSME sectors; however, these potentials have not been optimally managed due to limited human resource capacity, weak village economic institutions, low legal awareness, and the suboptimal role of the Village-Owned Enterprise (BUMDes). In addition, disparities in access to education, limited empowerment of women and vulnerable groups, and the lack of integrated management of the environment and village infrastructure remain significant challenges. Based on the SWOT analysis, the main strengths of the village lie in community openness and strong support from the village government for change, while the major challenges include low economic welfare and limited community capacity. This social mapping serves as a foundational basis for formulating sustainable village development strategies oriented toward strengthening human resources, optimizing local potential, reinforcing MSMEs, and improving participatory-based village governance.